1975
DOI: 10.1002/j.1879-3479.1975.tb00333.x
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopy: A Study of 500 Cases

Abstract: Kiser, R. E. and Newman, R. L. (St. Luke's Hospital, Kansas City, Missouri, USA).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1976
1976
1980
1980

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…(Interval sterilizations are those procedures performed at times other than those concomitant with abortion or delivery.) Selected international studies for colpotomy (Edwards & Hakanson 1973;Purandare 1974;Tappan 1973;Ashton 1974;Kashani, McCann & Vakilzadeh 1975;Yuzpe, Anderson, Cohen & West 1974;Wortman & Piotrow 1973), culdoscopy (Chen et 1974;Koetsawang 1974;Little 1972;Pacheco-Mena 1974;Lee 1975;El-Deen 1975;Mukerji & Chatterjee 1973;Cheng et al 1975), laparoscopy (Madrigal, Wallman & Goldsmith 1975;Edgerton 1974;Kleppinger 1974;Hughes & Liston 1975;Kiser & Newman 1975), and mini-laparotomy (Daissenaike 1976;Wortman 1974;Osathanondh 1974;Meyer & King 1975), were reviewed. Comparison of these studies indicates great variability in reporting of data because the meaning of terms and complications and the criteria by which they were determined have not been standardized.…”
Section: Morbidity and Failure Ratesmentioning
confidence: 99%
“…(Interval sterilizations are those procedures performed at times other than those concomitant with abortion or delivery.) Selected international studies for colpotomy (Edwards & Hakanson 1973;Purandare 1974;Tappan 1973;Ashton 1974;Kashani, McCann & Vakilzadeh 1975;Yuzpe, Anderson, Cohen & West 1974;Wortman & Piotrow 1973), culdoscopy (Chen et 1974;Koetsawang 1974;Little 1972;Pacheco-Mena 1974;Lee 1975;El-Deen 1975;Mukerji & Chatterjee 1973;Cheng et al 1975), laparoscopy (Madrigal, Wallman & Goldsmith 1975;Edgerton 1974;Kleppinger 1974;Hughes & Liston 1975;Kiser & Newman 1975), and mini-laparotomy (Daissenaike 1976;Wortman 1974;Osathanondh 1974;Meyer & King 1975), were reviewed. Comparison of these studies indicates great variability in reporting of data because the meaning of terms and complications and the criteria by which they were determined have not been standardized.…”
Section: Morbidity and Failure Ratesmentioning
confidence: 99%
“…Reports from these countries have shown that outpatient laparoscopy has high patient acceptance and is both safe and effective (2,5,9). While a number of investigators (1,3,4,6,8) from the United States continue to report on outpatient la-This paper was presented at the ¡978 Annual Meeting of the National Abortion Federation, San Francisco, CA, USA, September 24-26, 1978. paroscopy, it has not yet become a standard procedure. This report reviews a series of 1000 outpatient laparoscopic sterilization procedures performed on patients under local anesthesia at T h e Hope Clinic for Women, Ltd, Granite City, IL, USA.…”
Section: Introductionmentioning
confidence: 99%